S2k-Leitlinie zur Diagnostik, Therapie und Metaphylaxe der Urolithiasis (AWMF 043/025): Kurzfassung = S2k guidelines on diagnostics, therapy and metaphylaxis of urolithiasis (AWMF 043/025) - Knoll, Thomas; Stein, Raimund (Der Urologe, 2016)
Every tenth German citizen will suffer from at least one urinary calculus during the lifetime. The diagnostics, treatment and follow-up treatment of urolithiasis are, therefore, part of the daily routine practice for all urologists in hospitals and private practices as well as in many other disciplines, such as general practitioners, internists, nephrologists and pediatricians. Although the diagnostics and therapy have experienced substantial alterations over the last 10 years, the possibilities of metabolic diagnostics and secondary prevention for patients at risk are, unfortunately and unjustly, in many places very poorly represented. The present S2k guidelines, which for the first time were established in an interdisciplinary consensus process, represent the current practical recommendations and, whenever possible, use tables and algorithms in order to facilitate easy reference in the routine daily work. Last but not least, this greatly simplifies the measures for metaphylaxis.
Gesehen am 08.07.2019